The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1994
DOI: 10.1007/bf02411556
|View full text |Cite
|
Sign up to set email alerts
|

Flavin excretion from roots of iron-deficient sugar beet (Beta vulgaris L.)

Abstract: Abstract. The characteristics of flavin excretion from iron-deficient sugar-beet roots have been studied. Roots from iron-deficient sugar beet excreted flavins when plants were allowed to decrease the pH of the nutrient solution, but not when plants were grown in nutrient solutions buffered at high pH. As shown by reversedphase high-performance liquid chromatography, the two major flavins whose excretion was induced by iron deficiency were different from riboflavin, FMN and FAD. These flavins have been identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
1
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(63 citation statements)
references
References 27 publications
(34 reference statements)
2
58
1
2
Order By: Relevance
“…In the case of H. niger root cultures, the minimum pH was between 4.4~4.6 [36]. In sugar beet [34], pH reached approximately 3.7 after 15days, and pH was maintained at 3.5~4.0 in muskmelon [10]. In H. albus hairy roots, the minimum pH was around 4.0 when a single root tip was subjected to iron deficiency and around 4.5 when propagated roots did.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In the case of H. niger root cultures, the minimum pH was between 4.4~4.6 [36]. In sugar beet [34], pH reached approximately 3.7 after 15days, and pH was maintained at 3.5~4.0 in muskmelon [10]. In H. albus hairy roots, the minimum pH was around 4.0 when a single root tip was subjected to iron deficiency and around 4.5 when propagated roots did.…”
Section: Discussionmentioning
confidence: 98%
“…It was also found that not all but some strategy I plants from Aizoceae to Umbelliferae, including tobacco, beet, sunflower and cucumber, excrete riboflavin [39], and also unique riboflavin sulfates in the case of sugar beet [33,34], in the rhizosphere under iron-deficient conditions. Recently, cultured roots of Hyoscyamus niger were also found to be able to secrete riboflavin without their aerial parts [36].…”
Section: Introductionmentioning
confidence: 99%
“…Under Fe deficiency, the Arabidopsis plants secrete Fe-mobilizing phenolic compounds such as coumarins to acquire Fe by chelation and/ or reduction of Fe 3+ (Fourcroy et al 2014). Besides phenolics, some plant species such as sugar beet, spinach and alfalfa can synthesize and release abundant flavins that play redox and/or metal-complexing roles in augmenting Fe mobilization in the rhizosphere (Susín et al 1993(Susín et al , 1994Rodríguez-Celma et al 2011). Importantly, some PGPR strains such as Azospirillum brasilense and P. polymyxa BFKC01 can enhance Fe acquisition by increasing root-secreted phenolics (Pii et al 2015;Zhou et al 2016).…”
Section: Accumulated In Rootsmentioning
confidence: 99%
“…It is known that iron deficiency promotes the excretion of phenolic compounds, organic acids, and flavins, which also contribute to Fe reduction and solubility (Welkie and Miller, 1988;Susín et al, 1994). The FRO gene, is a key enzyme in Fe acquisition, and the first FRO2 gene was identified in the model plant Arabidopsis thaliana (Robinson et al, 1999).…”
Section: +mentioning
confidence: 99%